2016
DOI: 10.1038/leu.2016.363
|View full text |Cite
|
Sign up to set email alerts
|

Casein kinase 2 controls the survival of normal thymic and leukemic γδ T cells via promotion of AKT signaling

Abstract: The thymus is the major site for normal and leukemic T-cell development. The dissection of the molecular determinants of T-cell survival and differentiation is paramount for the manipulation of healthy or transformed T cells in cancer (immuno)therapy. Casein Kinase 2 (CK2) is a serine-threonine protein kinase whose anti-apoptotic functions have been described in various hematological and solid tumors. Here we disclose an unanticipated role of CK2 in healthy human thymocytes that is selective to the γδ T-cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 52 publications
2
13
0
Order By: Relevance
“…In addition, we showed that the combination of methotrexate and CX-4945 had a synergistic effect on the caspases 3/7 activation in CCRF-CEM cell line. The results are in agreement with the literature data demonstrating that CK2 and its substrates such as serine/threonine kinase AKT protect cells from apoptosis by phosphorylation of a wide range of proteins involved in the apoptotic response (30,31). Consequently, inhibition of CK2 leads to increased apoptosis in many types of cancer cells, including leukemia (32).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, we showed that the combination of methotrexate and CX-4945 had a synergistic effect on the caspases 3/7 activation in CCRF-CEM cell line. The results are in agreement with the literature data demonstrating that CK2 and its substrates such as serine/threonine kinase AKT protect cells from apoptosis by phosphorylation of a wide range of proteins involved in the apoptotic response (30,31). Consequently, inhibition of CK2 leads to increased apoptosis in many types of cancer cells, including leukemia (32).…”
Section: Discussionsupporting
confidence: 92%
“…Although we were unable to perform luciferase assays in primary murine 27 − T cells, we successfully validated Nod1 targeting by miR-146a in a human  T cell line ( fig. S7) that we previously showed to be a suitable model to study human  T cell development (28).…”
Section: Mir-146a Targets Nod1 Mrna That Is Depleted In 27 − T Cellsmentioning
confidence: 99%
“…Recent studies have shown that the developmental and proliferative programs as well as the expression of genes regulating apoptosis differ between the γδ and αβ lineages. 1,2 Certain neoplasms derived from the γδ T cell lineage such as primary cutaneous and hepatosplenic lymphomas are clinically aggressive with bleak prognoses and are recognized as being biologically distinct. [3][4][5][6][7][8] For patients with T-cell acute lymphoblastic leukemia (T-ALL) expressing the γδ TCR, case reports have suggested that they are at higher risk for poor outcomes.…”
Section: Introductionmentioning
confidence: 99%